Strategi Manajemen SDM dalam Mencapai Efektivitas dan Efisiensi Operasional - Pangestu, Yoga (Jurnal Administrasi Karya Dharma, 2025)
This research discusses human resource management strategies to increase the efficiency and effectiveness of organizational operations. This research uses a descriptive qualitative approach through a literature review related to theories, models and best practices in HR management. The results of the discussion show that strategies such as appropriate recruitment and selection, employee competency development through continuous training, performance- based rewards, and effective workload management play an important role in achieving operational efficiency. Utilization of technology, such as Human Resource Information Systems, helps speed up administrative processes and support strategic decision making. Additionally, employee training and development allows organizations to remain relevant to the changing external environment. Challenges identified include resistance to change and lack of leadership support, which requires data-driven solutions and strategic adaptation. This study emphasizes the importance of integrating HR strategy in organizational management to increase competitiveness in a dynamic market.